He-doped pseudospark as a home-lab XUV source beyond the beamtime bottleneck. (14th February 2017) - Arbelo, Yunieski; Barbato, Francesco; Bleiner, Davide
Abstract: A table-top XUV-source based on pseudospark plasma-emission is operated with pure gases (Ar, O2 and N2 ) and mixtures (Ar/He, O2 /He and N2 /He) at different pressures and input voltages, and the dependence of these parameters on the source repetition rate, XUV-photon flux, XUV-power and emission spectra are discussed. Operating the source with Ar, it is shown that the repetition rate is increased if the pressure or input voltage from the power supply are increased. The intensity on the spectra and XUV photon flux (for Ar and Ar/He) are observed to decrease with increment of pure gas pressure and to increase with the addition of He to the pure gases. Repetition rates of up to 25 Hz and 10 13 photons/( 2 π sr pulse) for λ between 7 and 16 nm and XUV-power of up to 10 mW/( 2 π sr) have been observed. Stability measurements and determination of optimal sample position with respect to the highest number of photons are also presented. Fluctuations on the plasma emission up to 10% are observed.